Learning OpenCV, 2nd Edition - Kaehler, Adrian; Bradski, Gary (O'Reilly Media, Incorporated, 2014)
Learning OpenCV puts you in the middle of the rapidly expanding field of computer vision. Written by the creators of the free open source OpenCV library, this book introduces you to computer vision and demonstrates how you can quickly build applications that enable computers to "see" and make decisions based on that data. The second edition is updated to cover new features and changes in OpenCV 2.0, especially the C++ interface.